2010
DOI: 10.1089/sur.2009.029
|View full text |Cite
|
Sign up to set email alerts
|

Microbiology of Surgical Site Infections Complicating Breast Surgery

Abstract: Although the usual empiric treatment of SSI after breast surgery targets staphylococci, cultures with susceptibility profiles should be obtained because non-staphylococcal bacteria were commonly identified, and drug resistance was seen in more than one-half of the isolates. Further study is needed to define the optimal empiric antibiotic therapy for SSI after breast surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
12
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 15 publications
9
12
0
1
Order By: Relevance
“…These findings are in agreement to another study [18]. This study found more MDR among Gram-negative bacteria than Gram-positive bacteria; of these the proportion of MRSA (37.5%) among S. aureus isolates was more than previously reported (25.0% and 31.5%) from Uganda [9,21] and other countries [8,16,18]. Thus, while β-lactamase-resistant antibiotics such as cloxacillin could still be effective in this setting, they are likely to be ineffective against the 38% of isolates that were confirmed as MRSA.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are in agreement to another study [18]. This study found more MDR among Gram-negative bacteria than Gram-positive bacteria; of these the proportion of MRSA (37.5%) among S. aureus isolates was more than previously reported (25.0% and 31.5%) from Uganda [9,21] and other countries [8,16,18]. Thus, while β-lactamase-resistant antibiotics such as cloxacillin could still be effective in this setting, they are likely to be ineffective against the 38% of isolates that were confirmed as MRSA.…”
Section: Discussionsupporting
confidence: 92%
“…These infections pose therapeutic challenges and are associated with substantially longer duration of hospital stay, increased hospital cost, higher morbidity and mortality [5,12], particularly when the agents are Methicillin resistant S. aureus (MRSA), Extended spectrum beta lactamase (ESBL) producing Enterobacteriaceae and/or other agents collectively referred to as multidrug-resistant (MDR) [11,13,14]. Studies from developing countries have shown high level of resistance (ranging from 50 to 100%) to the commonly used antibiotics like ampicillin, trimethoprim – sulphamethoxazole, gentamicin, chloramphenicol and third generation cephalosporins among S. aureus, E. coli , and P. aeruginosa [8,15] as opposed to low rates of resistance ranging from 0-50% in developed countries [16]. In both settings however, substantial rates of resistance to oxacillin, erythromycin and clindamycin reported for S. aureus, ranged from 10-60% [8,9,15,16] whereas vancomycin (for S. aureus and other Gram-positive bacteria ), amikacin, piperacillin-tazobactam and imepenem (for E. coli , P. aeruginosa and other Gram-negative bacteria) showed resistant rates of less than 25% [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies reported the same results [8, 15]. However, Mukhtar et al [16] reported Gram negative bacteria as the most common isolated pathogens.…”
Section: Discussionsupporting
confidence: 58%
“…Secondly, timing and incidence of infection during the months/years after surgical implantation have been variably studied so far, predominantly with retrospective studies that consider either constrained observation periods or mixed breast implant infections with other surgical infections [4][5][6][7][8]. Accordingly, there are good indications on the factors associated with this occurrence, particularly early after implant insertion.…”
mentioning
confidence: 99%